2016
DOI: 10.1152/jn.00028.2016
|View full text |Cite
|
Sign up to set email alerts
|

Whisker-related afferents in superior colliculus

Abstract: Rodents use their whiskers to explore the environment, and the superior colliculus is part of the neural circuits that process this sensorimotor information. Cells in the intermediate layers of the superior colliculus integrate trigeminotectal afferents from trigeminal complex and corticotectal afferents from barrel cortex. Using histological methods in mice, we found that trigeminotectal and corticotectal synapses overlap somewhat as they innervate the lower and upper portions of the intermediate granular lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…Since the ChR2-labeled V1 axons contained the Cre virus, the functional coupling between the former and the transneuronally labeled striatal neurons provides strong evidence for transsynaptic spread of the Cre virus to synaptically connected target neurons. To further support this notion, our control experiments (Castro-Alamancos and Favero, 2016) demonstrated that the LED-evoked current was only synaptic in nature, as antagonists of glutamate receptors completely blocked the current (Figure S3). …”
Section: Resultsmentioning
confidence: 71%
“…Since the ChR2-labeled V1 axons contained the Cre virus, the functional coupling between the former and the transneuronally labeled striatal neurons provides strong evidence for transsynaptic spread of the Cre virus to synaptically connected target neurons. To further support this notion, our control experiments (Castro-Alamancos and Favero, 2016) demonstrated that the LED-evoked current was only synaptic in nature, as antagonists of glutamate receptors completely blocked the current (Figure S3). …”
Section: Resultsmentioning
confidence: 71%
“…In addition, intermediate and deeper layers of SC also receive sensory information from the whiskers, via a projection from vS1 as well as directly via the trigeminal nucleus of the brainstem 8,20,21 . While several studies have shown that SC neurons are directly activated by whisker deflections 6,22 , it is not known whether activation of SC modulates coding of whisker input in vS1. This issue is the focus of the current study.…”
mentioning
confidence: 99%
“…It is well established that SC receives direct input from the primary sensory cortices [4][5][6][7][8][9] . What is less clear is whether SC, in turn, modulates information processing in the cortex.…”
mentioning
confidence: 99%
“…It is well established that SC receives direct input from the primary sensory cortices (Welker et al, 1988;May, 2006;Cohen et al, 2008;Triplett et al, 2012;Castro-Alamancos & Favero, 2016;Zingg et al, 2017). What is less clear is whether SC in turn modulates information processing in the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory information from the whiskers is processed by the whisker associated area of the somatosensory cortex, known as the primary vibrissal somatosensory cortex (vS1 ;Brecht 2007;Diamond & Arabzadeh 2013). In addition, intermediate and deeper layers of SC also receive sensory information from the whiskers, via a projection from vS1 as well as directly via the trigeminal nucleus of the brainstem (Wise & Jones, 1977;Killackey & Erzurumlu, 1981;Bosman et al, 2011;Triplett et al, 2012;Castro-Alamancos & Favero, 2016). While several studies have shown that SC neurons are directly activated by whisker deflections (Dräger & Hubel, 1976;Castro-Alamancos & Favero, 2016), it is not known whether activation of SC modulates coding of whisker input in vS1.…”
Section: Introductionmentioning
confidence: 99%